PENINGKATAN HASIL BELAJAR DAN AKTIVITAS BELAJAR PELAJARAN SOSIOLOGI DENGAN MODEL COURSE REVIEW HORAY (CRH) DI KELAS XI IPS 1 SMAN 1 GEBOG KUDUS - Rakhmawati, Erna Dwi (IJTIMAIYA: Journal of Social Science and Teaching, 2019)
The aim of this study is to address the problem of learning in the classroom by using Course Review Horay (CRH) model. The problems of learning  in the class XI IPS 1, as a scope of this study, is very low level of learning activities in sociology which also resulted in low level of the learning outcomes. The measure of the success of learning outcomes is KKM (Kriteria Ketuntasan Minimal/ Criterion for Minimum Completeness). The KKM of class XI IPS 1 SMAN 1 Gebog Kudus is 65. The design of this study is CAR (Classroom Action Research) or PTK (Penelitian Tindakan Kelas). This study was done in a cyclical way, using CRH learning model. The results of the research in cycle 1 show that the average of student’s activities in learning is 81.49% and is categorized as good. Student learning outcomes classically who reached the KKM amounted to 84.62% of the total students in the class, while the others 15.38%  have not reached the KKM. The classical mastery learning in cycle 1 has not been reached. The suggestions from supervisors and collaborators at the end of cycle 1 as a reflection inputs, will be used to improve the quality of teaching process in the next cycle. The results of the research in cycle 2 show that the average of student’s activities in learning process is 82.94% and is categorized as good. The classical learning outcomes show that 88.46% of the students reached the KKM, while 11.54% of the students have not reached the KKM. In cycle 2, the classical mastery learning has been achieved. The student’s responses show that 100% of the students are interested in learning model that is applied, or in K13, known as mastery learning. Students who have not complete or reached the KKM will take remedial learning test based on the achievement of learning objectives and indicators. While for the students who have completed study, we will conduct the enrichment.